Case Report: Thoracoscopic treatment of infradiaphragmatic pulmonary sequestration and intrathoracic kidney associated with congenital diaphragmatic hernia - Guo, Rui; Dong, Chunhua; Zhai, Yunpeng; Zhao, Huashan; Lv, Longfei; Zhang, Shisong (Frontiers in Pediatrics, 2024)
Background: Congenital pulmonary sequestration is a rare lung anomaly that can be classified as intralobar pulmonary sequestration or extralobar lung sequestration (ELS). Infradiaphragmatic pulmonary sequestration is a rare type of ELS. Furthermore, intrathoracic kidney (ITK) is a rare disease that can be associated with a congenital diaphragmatic hernia (CHD) in 0.25% of cases. We report the first case of infradiaphragmatic pulmonary sequestration and ITK associated with CDH in a child. Case report and management: The patient, male, aged 6 months, visited our hospital 2 months prior due to shortness of breath. Based on chest ultrasonography and enhanced computed tomography (CT) examination, infradiaphragmatic pulmonary sequestration and ITK were